The Impact of Enabling Programs on Indigenous Participation, Success and Retention in Australian Higher Education - Pitman, Tim; Harvey, A.; McKay, J.; Devlin, M.; Trinidad, S.; Brett, M. (2017)
This chapter details the findings from a national project that investigated the efficacy of the enabling program pathway into higher education for disadvantaged student groups. Enabling programs are not-for-degree programs designed to provide the necessary academic and cultural scaffolding for students who do not meet the institution’s usual admissions criteria. The brief given to the project team was to undertake a review of current enabling programs offered by Australian higher education providers and report on the extent to which these courses were effective in increasing access and participation to, and subsequent success in, undergraduate courses for domestic students from disadvantaged groups. This chapter focuses specifically on the findings relevant to Indigenous students, who represent one of six officially recognised equity groups of students in Australian higher education policy. In this chapter the authors detail and discuss the nature and design of enabling programs for Indigenous students, and then provide a detailed analysis of the first year retention and success rates for Indigenous students who transitioned to undergraduate studies via these enabling programs. The evidence from the study indicates that Indigenous enabling pathways provide an important and effective environment in which the students develop a sense of belonging in higher education and develop the necessary resilience to persist in their subsequent studies. However, it is less clear whether Indigenous students are receiving the academic skills development necessary to succeed in their studies at rates similar to other students.